ANALISIS PERILAKU PENGADUAN KONSUMEN MELALUI YAYASAN LEMBAGA KONSUMEN INDONESIA (YLKI) DAN HARIAN KOMPAS TAHUN 2007 - Moh. Djemdjem Djamaludin; Henny Rochany; Megawati Simanjuntak (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2008)
The general objective of this study was to analyze consumer’s complaint behavior through Indonesia Consumer Organization and Kompas Daily in 2007. This study used a traditional approach analysis and behavior approach of consumer’s loyalty. Data were collected from February to May 2008, located in Jakarta-Bogor-Depok-Tangerang-Bekasi (JABODETABEK). The case report of descriptive consumer study was used in collecting secondary data obtained by Indonesian Consumer Organization and Kompas Information Centre. Frequency and descriptive statistics were used to analyze single variable. Cross tabulations and Chi Square were utilized to examine the relation between two variables. The results of study showed that the highest percentage of sample had told disappointment to their friend or relatives. Generally, based on the respond of the company or shop, samples were satisfied with the action, speed, and completeness in complaint handling. Almost 75% samples were still loyal after process of complaint handling. There were significant relation between personal action (utilizing good or service during complaint handling) and satisfaction of respond and speed in handling complaint. There was significant relation between: gender and loyalty, and also between loyalty and satisfaction of action in complaint handling.